Sildenafil is more selective pulmonary vasodilator than prostaglandin E1 in patients with pulmonary hypertension due to heart failure - Al-Hiti, H; Melenovský, V; Syrovátka, P; Kettner, J; Málek, I; Kautzner, J (Physiological research, 2011)
In some patients, heart failure (HF) is associated with increased pulmonary vascular resistance (PVR). The magnitude and the reversibility of PVR elevation affect the HF management. Sildenafil has been recently recognized as potent PVR-lowering drug in HF. The aim of the study was to compare hemodynamic effects and pulmonary selectivity of sildenafil to prostaglandin E(1) (PGE(1)). Right-heart catheterization was performed in 13 euvolemic advanced HF patients with elevated PVR (6.3+/-2 Wood's units). Hemodynamic parameters were measured at the baseline, during i.v. infusion of PGE1 (alprostadil 200 ng · kg(-1) · min(-1)) and after 40 mg oral dose of sildenafil. Both drugs similarly reduced systemic vascular resistance (SVR), but sildenafil had higher effect on PVR (-28 % vs. -49 %, p = 0.05) and transpulmonary pressure gradient than PGE(1). The PVR/SVR ratio--an index of pulmonary selectivity, did not change after PGE(1) (p = 0.7) but it decreased by -32 % (p = 0.004) after sildenafil. Both drugs similarly reduced pulmonary artery mean and wedge pressures and increased cardiac index (+27 % and +28 %). Sildenafil led more often to transplant-acceptable PVR while causing smaller drop of mean systemic pressure than PGE(1). In conclusion, vasodilatatory effects of sildenafil in patients with heart failure are more pronounced in pulmonary than in systemic circulation.
Keywords: Vascular Resistance; Humans; Sildenafil Citrate; Heart Failure; srdeční selhání; lidé středního věku; vazodilatancia; sildenafil citrát; Sulfones; plicní tlak v zaklínění; Female; dospělí; Cardiac Output; Purines; lidé; minutový srdeční výdej; Hypertension, Pulmonary; cévní rezistence; Adult; plicní hypertenze; ženské pohlaví; Male; Middle Aged; alprostadil; sulfony; puriny; piperaziny; srdeční katetrizace; Cardiac Catheterization; Alprostadil; Piperazines; Vasodilator Agents; arteria pulmonalis; mužské pohlaví; Pulmonary Wedge Pressure; Pulmonary Artery